2018
DOI: 10.1016/j.clinph.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine promotes biomimetic non-rapid eye movement stage 3 sleep in humans: A pilot study

Abstract: These results suggest that α2a adrenergic agonists may be developed as a new class of sleep enhancing medications with neurocognitive sparing benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(82 citation statements)
references
References 55 publications
1
76
0
Order By: Relevance
“…It is worth noting that in certain states, such as anesthesia or epilepsy 90 , cells in the thalamus may fire at the population rhythm, and sparse synchronicity in the thalamus might be a distinguishing feature of normal resting states 91 . The disruption of thalamocortical oscillations has been proposed as a pathophysiological model for several neuropsychiatric disorders 92,93 .…”
Section: Sparse Firing Of Thalamic Cells During Spindles and Its Rolementioning
confidence: 99%
“…It is worth noting that in certain states, such as anesthesia or epilepsy 90 , cells in the thalamus may fire at the population rhythm, and sparse synchronicity in the thalamus might be a distinguishing feature of normal resting states 91 . The disruption of thalamocortical oscillations has been proposed as a pathophysiological model for several neuropsychiatric disorders 92,93 .…”
Section: Sparse Firing Of Thalamic Cells During Spindles and Its Rolementioning
confidence: 99%
“…Studies involving dexmedetomidine for sleep promotion uniformly demonstrate increased N2, [163][164][165] with inconsistent findings regarding SE and N3/SWS. 163,164,166,167 Furthermore, one study demonstrated presence of sleep spindles in patients receiving dexmedetomidine, arguing for its role in approximating "natural sleep." 165 To our knowledge, no study has demonstrated improvement in REM with dexmedetomidine.…”
Section: Dexmedetomidinementioning
confidence: 99%
“…On entering NREM sleep, the neocortex of rats and mice cools rapidly (33,34). NREM sleep and low body temperature can also be brought together pharmacologically: a2 adrenergic agonists induce an arousable NREM sleep-like profile 5 (26,(35)(36)(37)(38), which in humans resembles stage 2/3 NREM sleep (39)(40)(41), but with the complication of sustained hypothermia (26,35). The metabotropic a2A receptor mediates both the NREM sleep-like state and the hypothermic effects of dexmedetomidine (42,43).…”
Section: Introductionmentioning
confidence: 99%